(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2025)
Modern education increasingly faces a crisis of morality and a decline in spiritual depth among learners, indicating the need for a more holistic character education model grounded in religious values. This study aims to analyze the humanistic Hindu values in the Krishna–Arjuna dialogue of the Bhagavad Gita and formulate a conceptual model of spiritual character education relevant to contemporary contexts. This research employs a qualitative-descriptive approach through library research, content analysis, and textual hermeneutics to interpret the humanistic values embedded in the text and their relevance for education. The findings reveal six fundamental values karuna, satya, dama, kshanti, abhaya, and nishkama karma which serve as the foundation for spiritual character development. These values align with contemporary educational theories such as Transformative Learning, Humanistic Education, and Character Education, enabling a strong integration between Hindu spirituality and modern pedagogy. The study proposes a conceptual model consisting of value dimensions, dialogical-reflective methods, contemplative practices, ethical case-based learning, and behavioral actualization through self-observation and selfless action. The implications highlight the significance of the Bhagavad Gita as a philosophical and pedagogical foundation for strengthening Hindu religious education, enhancing teacher competence, and cultivating morally and spiritually mature learners.